Do We See Masculine Faces as Competent and Feminine Faces as Warm? Effects of Sexual Dimorphism on Facial Perception. (23rd November 2020) - Wen, Fangfang; Zuo, Bin; Ma, Shuhan; Xu, Yian; Coley, John D.; Wang, Yang
Previous research on non-facial features demonstrated that masculinity and femininity correlated highly with perceived competence and warmth, respectively. Several studies focused on dimorphic facial cues and found an association between masculine faces and competence. However, there's no study exploring the association between facial dimorphism and social judgment both using explicit and implicit experimental paradigms, i.e. Triad Classification Task, Implicit Associate Task. This study examined the association of masculinity/femininity and competence/warmth via explicit and implicit measures in three experiments. The results showed that participants saw feminine/masculine faces as more consistent with warmth/competence for both male and female faces. Besides, it was found that the above associations were more obvious in female participants. The current studies extended research of effects of dimorphic facial cue in social judgment and provided direct evidence linking facial masculinity with perceived competence, and facial femininity with perceived warmth.